PENGARUH PIUTANG DAGANG DAN METODE PENCATATAN TERHADAP KETERSEDIAAN MODAL PENJUALAN DALAM PERSPEKTIF EKONOMI ISLAM PADA TOKO ANAN DESA KARYA MUKTI - Binti Nurchasanatul Jajiyah; El Munawwarah; Raden Hebat Kurnia (CV. KAMPUS AKADEMIK PUBLISING, 2025)
This study aims to evaluate how accounts receivable and recording methods influence the availability of sales capital at Toko Anan in Karya Mukti Village, within the framework of Islamic economics. The research adopts a mixed-method approach, combining quantitative techniques with qualitative analysis. Data were collected from 100 respondents, with 33 samples used for instrument testing and 67 for multiple linear regression analysis using SPSS 20.0. The results indicate that accounts receivable have a significant effect on sales capital (t-count 3.807 > t-table 1.668), as do recording methods (t-count 2.607 > t-table). These findings highlight the importance of accurate recording systems and the management of receivables based on principles of justice, transparency, and trust in Islamic economics.